A Visible‐Light‐Mediated Radical Smiles Rearrangement and its Application to the Synthesis of a Difluoro‐Substituted Spirocyclic ORL‐1 Antagonist. Issue 49 (16th October 2015) - Douglas, James J.; Albright, Haley; Sevrin, Martin J.; Cole, Kevin P.; Stephenson, Corey R. J.
Abstract: A visible‐light‐mediated radical Smiles rearrangement has been developed to address the challenging synthesis of the gem ‐difluoro group present in an opioid receptor‐like 1 (ORL‐1) antagonist that is currently in development for the treatment of depression and/or obesity. This method enables the direct and efficient introduction of the difluoroethanol motif into a range of aryl and heteroaryl systems, representing a new disconnection for the synthesis of this versatile moiety. When applied to the target compound, the photochemical step could be conducted on 15 g scale using industrially relevant [Ru(bpy)3 Cl2 ] catalyst loadings of 0.01 mol %. This transformation is part of an overall five‐step route to the antagonist that compares favorably to the current synthetic sequence and demonstrates, in this specific case, a clear strategic benefit of photocatalysis. Abstract : A reason for Smiles : A visible‐light‐mediated radical Smiles rearrangement addresses the challenging synthesis of the gem ‐difluoro group present in an opioid receptor‐like 1 (ORL‐1) antagonist and enables the introduction of the difluoroethanol motif into a range of aryl and heteroaryl systems. When applied to the target compound, the photochemical step could be conducted on 15 g scale at a [Ru(bpy)3 ]Cl2 loading of 0.01 mol %.